AB0410 Pregnancy and Anti-TNFα Drugs: Experience of Four Centres. (9th June 2015) - Hoxha, A.; Calligaro, A.; Favaro, M.; Di Poi, E.; Del Ross, T.; Ramonda, R.; Peccatori, S.; Grava, C.; Raffeiner, B.; Ruffatti, A.; Punzi, L.
Abstract : Background: The introduction of biologic therapies has significantly improved the outcome of inflammatory rheumatic diseases. As most of these diseases affect women and men in childbearing age there is concern about safety of biologic drugs during reproduction and pregnancy. Objectives: To evaluate the effects of anti-TNFα agents on pregnancy and foetal outcome. Methods: We conducted a retrospective multicentre study of 24 women and 2 men with rheumatoid arthritis (RA), ankylosing spondylitis (AS) and psoriatic arthritis (PsA), respectively. They were treated with anti-TNFα agents prior to conception or until conception/during pregnancy. Data were collected from four Centres (Belluno, Padua, Trento and Udine). A 28-question chart abstraction form was filled by the treating rheumatologist. The primary outcome was the occurrence of congenital malformations. Secondary outcomes were the rate of premature birth (defined as <37 weeks of gestation), small for gestational age (defined as <10th percentile) and the occurrence of vaccine complications. Results: Until to 31st December 2014, a total of 32 pregnancies were registered, including one twin pregnancy; 5 women had multiple pregnancies. Twenty-four/32 (75%) pregnancies were exposed to anti-TNFα agents at conception or during pregnancy; 21 of these (87.5%) pregnancies occurred following maternal exposure and 3 (12.5%) following paternal exposure. While 8/32 (25%) pregnancies, following leaflet recommendations, had suspended the therapy before conception. An overview of pregnancies following maternal exposure is reported in table 1 . One infant was diagnosed with congenital diaphragmatic hernia and obstructive megaureter; the mother was exposed to adalimumab (ADA) at conception and developed preeclampsia at 33 week of gestation (WG). One infant was diagnosed with cystic fibrosis at 3 months of age; the mother was exposed to etanercept (ETN) at conception. One mother exposed to certolizumab (CZP) at conception underwent caesarean section at 35 WG due to preterm premature rupture of membranes. Two mothers exposed to ETN at conception developed a vanishing syndrome and a post-partum infection, respectively. There was no significant difference concerning gestational age and birth weight, both between the group exposed to anti-TNF-alpha at conception and that exposed before conception and, between the groups exposed to different anti-TNFα agents. Seventeen out of 21 infants (80.9%) underwent vaccinations according to national schedule. None of them have any vaccine complications. The pregnancies following paternal exposure were all in ETN. All pregnancies ended in live births. There was one infant with intrauterine growth restriction. The baby was admitted for 14 days to the neonatal intensive care unit for respiratory distress. Conclusions: Maternal exposure to anti-TNFα at conception was not associated with an increased risk of congenital malformation and/or with other adverse outcomes. Also the exposure to anti-TNFα in men at time of conception was not associated with any adverse outcome in their partners or newborns. Disclosure of Interest: None declared